2015
DOI: 10.1002/hbm.22808
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of white matter microstructure in alcoholics with and without Korsakoff's syndrome

Abstract: Alcohol dependence results in two different clinical forms: "uncomplicated" alcoholism (UA) and Korsakoff's syndrome (KS). Certain brain networks are especially affected in UA and KS: the frontocerebellar circuit (FCC) and the Papez circuit (PC). Our aims were (1) to describe the profile of white matter (WM) microstructure in FCC and PC in the two clinical forms, (2) to identify those UA patients at risk of developing KS using their WM microstructural integrity as a biomarker. Tract-based spatial statistics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 92 publications
3
28
0
Order By: Relevance
“…1) within similar tracts previously reported (Pfefferbaum et al, 2006; Harris et al, 2008; Durkee et al, 2013; Pfefferbaum et al, 2014; Segobin et al., 2015; Sorg et al, 2015). The FA deficits imply disruptions in these fibers due to axonal deletion (de la Monte et al, 2014), demyelination (Pfefferbaum and Sullivan, 2005), and/or microtubule disruptions (Mayfield et al, 2002), which can impair inhibitory control (Baler and Volkow, 2006), working memory, and visuospatial performance in alcohol-dependent individuals (Pfefferbaum et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1) within similar tracts previously reported (Pfefferbaum et al, 2006; Harris et al, 2008; Durkee et al, 2013; Pfefferbaum et al, 2014; Segobin et al., 2015; Sorg et al, 2015). The FA deficits imply disruptions in these fibers due to axonal deletion (de la Monte et al, 2014), demyelination (Pfefferbaum and Sullivan, 2005), and/or microtubule disruptions (Mayfield et al, 2002), which can impair inhibitory control (Baler and Volkow, 2006), working memory, and visuospatial performance in alcohol-dependent individuals (Pfefferbaum et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…We applied TBSS for determining microstructural differences between treatment-seeking alcohol-dependent individuals and light drinkers: FA was lower in fibers within frontal WM, limbic pathways, and between cortico-striatal regions; in the small group of patients, associations between drinking severity and regional FA were insignificant (Yeh et al, 2009). Other TBSS studies in alcohol dependence reported FA deficits specifically within cingulum, corpus callosum, fornix (Durkee et al, 2013; Trivedi et al, 2013; Pfefferbaum et al., 2014; Smith et al, 2015; Sorg et al, 2015), and superior longitudinal fasciculus (Pfefferbaum et al, 2014; Segobin et al, 2015). Microstructural abnormalities were most pronounced in major tracts within frontal WM (Fortier et al, 2014; Pfefferbaum et al, 2014; Sorg et al, 2015) and related to higher lifetime alcohol consumption (Sorg et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown white matter alterations in prefrontal and mesocorticolimbic circuits (Oscar-Berman et al, 2014; Schulte et al, 2010; Segobin et al, 2015) in association with chronic alcoholism. However, other systems such as the language system and visuospatial attention are also impaired (Fitzpatrick et al, 2008; Mlinarics et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have focused on regions within the Extended Reward and Oversight System (Moselhy, Georgiou, & Kahn, 2001, Oscar-Berman et al, 2014; Schulte, Muller-Oehring, Pfefferbaum, & Sullivan, 2010; Segobin et al, 2015), other alterations, e.g., of the corpus callosum (Ruiz et al, 2013), as well as superior longitudinal fascicles I and II and arcuate fascicle, have been reported to be altered in chronic alcoholism (Harris et al, 2008). In the later study, our team interestingly also found abnormalities in postrolandic areas such as the right superior temporal gyrus using exploratory voxel-based analyses of FA.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-related cognitive defects may lead to poor participation in therapeutic workshops or absence of recording of therapeutic advice [17], thus impairing the global efficacy of rehabilitation programs. Another key factor in recovery is preservation of complete abstinence, although recent neuroimaging data suggest that certain brain regions might recover even if patients resume drinking small amounts [18]. As any lapse or relapse is difficult to detect and as report of abstinence is typically based on declarative or self-report data, interpretation of longitudinal studies of outpatients requires caution.…”
Section: Introductionmentioning
confidence: 99%